(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Advice-giving means offering guidance or recommendations offered with regard to prudent future action. The individuals vary in their methods of offering advice. Such differences might be attributed to the cultural differences. Therefore, the present study aims to investigate the cross-cultural differences in advice-giving strategies among Jordanian and British speakers. It aims to examine the types of advice-giving strategies employed by Jordanian speakers and British speakers. It investigates the effect of gender, and social power and distance (=, +) on advice-giving among Jordanian speakers and British speakers. The study further seeks to identify the degree of politeness among the Jordanian speakers and British speakers in offering advice. To this end, a total of (60) participants are divided into two groups; (30) Jordanian speakers and (30) British speakers. Each group consists of (15) males and (15) females. To analyze the data, Hinkel’s (1997) taxonomy of advice-giving strategies, direct, indirect, and hedge as well as Brown and Levinson’s (1987) politeness theory are used. Hinkel multiple choice questionnaire consists of (8) situations; (4) of them pertained to advice-giving for peer, whereas (4) of them pertained to advice-giving for instructors. As for giving advice for peers, the findings reveal that Jordanian speakers used direct advice-giving strategies, while British speaker used indirect advice-giving strategies. As for advice giving for instructors, British speakers used more indirect giving strategies than Jordanian speakers, whereas Jordanian speakers used more hedge advice giving strategies than British speakers. The advice-giving strategies, whether indirect or hedge fall under politeness strategies. Regarding the gender differences in using advice-giving strategies, the results show that Jordanian male speakers were inclined towards using direct advice giving strategies more than females. The finding reveal that females used indirect, hedge, and polite advice-giving strategies, while males used direct and impolite advice-giving strategies. The study recommends investigating advice-giving among other cultures such as between Asian speakers and Jordanian speakers.